2020
DOI: 10.1302/0301-620x.102b11.bjj-2020-0610.r2
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility total hip arthroplasty in the treatment of femoral neck fractures

Abstract: Aims To evaluate the rate of dislocation following dual mobility total hip arthroplasty (DM-THA) in patients with displaced femoral neck fractures, and to compare rates of dislocation, surgical-site infection, reoperation, and one-year mortality between DM-THA and bipolar hemiarthroplasty (BHA). Methods Studies were selected based on the following criteria: 1) study design (retrospective cohort studies, prospective cohort studies, retrospective comparative studies, prospective comparative studies, and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
0
15
0
2
Order By: Relevance
“…Consideration of dual mobility or constrained liner in patients with dementia who cannot follow postoperative instructions is also recommended. [24][25][26]…”
Section: E133mentioning
confidence: 99%
“…Consideration of dual mobility or constrained liner in patients with dementia who cannot follow postoperative instructions is also recommended. [24][25][26]…”
Section: E133mentioning
confidence: 99%
“…35,36 Our findings of similar dislocation rates after DMC-THA compared with HA, are at odds with the small clinical studies and the pooled meta-analysis on patients with a fracture of the hip with or without neurological disease, comparing the dislocation rate between HA and DMC-THA. 20,37 A register study from the Nordic countries showed a reduced risk of revision with DMC-THA as treatment for a fracture, compared with cTHA, with the limitation of not having comorbidity data to adjust for, and without information about neurological diseases. 18 The place of DMC-THAs in the treatment of patients with a fracture is nowadays clear, though it is not a 'magic bullet', as illustrated by our finding of a similar risk of revision and reoperation as cTHA and HA in our high-risk group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] In patients with a femoral neck fracture, the use of dualmobility components (DMC-THA) has increased at the expense of conventional THA (cTHA), although observational studies have suggested that this type of implant confers a reduced risk of dislocation. [14][15][16][17][18][19][20] While the importance of the size of the femoral head has been well described in elective primary THA, it has been less well described in arthroplasty for fractures of the hip. [21][22][23][24] It has been shown that the posterior approach is associated with a higher risk of dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…Coomber et al published a review of the evi­dence on technique for performing THA for hip fracture and recommend the use of larger head sizes (32 mm to 36 mm) [ 21 ]. Dual mobility components have been shown to reduce the risk of dislocation further in patients with a femoral neck fracture [ 22 ].…”
Section: Discussionmentioning
confidence: 99%